Voice Onset Time (VOT) and Vowel Duration - Veniranda, Yohana (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
This study investigates the effects of voicing of a preceding and following plosive on the Voice Onset Time (VOT) and vowel duration. The data consist of words with CVC segments, with the four groups of samples that represent both voiced and voiceless plosives, both for the ones following and preceding the vowels. The preliminary hypothesis is that voicing of following plosives affects the length of the vowels, indicated by the vowel duration, and VOT is affected by the voicing of thepreceding plosives, not the following plosives. To compare the effects of voicing on the lengths of the vowel duration and VOT, the sound files are analyzed using the Praat program. The results of this study show that the voicing of the following plosives affects the vowel duration, while the voicing of the preceding plosives does not affect the vowel duration. The results also show that it is the voicing of the C1 plosives that affect the VOT. The word-ending plosives do not affect the VOT of the preceding plosives.This study is on English vowel duration and VOT affected by the following and preceding stops. A further study can be done to compare the results of the effects with another language.